Retention in school - Cláudia Ribeiro da Silva (Instituto Politécnico de Viseu, 2021)
Introduction: In Portugal, the retention in school presents worrying figures. The indicator "Direct Paths to Success", created by the Ministry of Education, shows that the majority of students who did not finish secondary school in 2019 was because they failed a year or had a negative score in at least one of the national exams. Out of a universe of 456,368 students, only 201,937 (44%) had the so-called "direct success path". (Source: http://infoescolas.mec.pt/ 02/2019)